Michika Chiefdom: A Brief History of Existence, Resistance, and Restoration - Kwaji, Joseph T. (Darul Yasin Al Sys, 2026)
Michika is a traditional kingdom located in the Mandara Mountains of northeastern Nigeria and serves as the historical and cultural center of the Kamwe (Higi) people. Established around 1200 CE, the Michika Kingdom has played a crucial role in the political, judicial, administrative, and spiritual life of the Kamwe community, while maintaining active diplomatic and commercial relations with other regional powers, including the Borno Empire under Mai Idris Alooma. According to oral tradition, the Kamwe trace their ancestry to a legendary figure named Gelmai, who is believed to have migrated from Ethiopia around 900 CE. His descendants founded early settlements such as Sukur, Sina, and Zah, which formed the genealogical foundation of Kamwe leadership and culminated in the establishment of Michika by Kwada Kwaka around 1450 CE. Despite colonial pressures from British, German, and French forces—often allied with Fulani elites—the Kamwe people preserved their sociopolitical structures and cultural identity. Michika is also noted for its resistance to Islamization and slave raids, as documented by European explorers and local slave raiders such as Hama Yaji. Economically, Michika thrived through trade in agricultural produce and iron ore, particularly supported by the Lighyei artisan class renowned for blacksmithing. The 21st-century restoration of the Michika Kingdom under the leadership of His Royal Highness Prof. Bulus Luka Gadiga marks a resurgence of Kamwe customary sovereignty and a rejection of colonial and Fulani-centric narratives that have historically marginalized local histories. This study affirms that the Michika Kingdom is one of the oldest indigenous political institutions in Nigeria, now reasserting its identity as a symbol of cultural resilience, local autonomy, and historical reclamation.